Biozonation of Sinemurian and Pliensbachian larger benthic foraminifera (Velebit Mt., Croatia) - Veseli, Vladimir; Velic, Ivo; Vlahovic, Igor; Tisljar, Josip; Stankovic, Damir (Anuário do Instituto de Geociências, 2006)
Abstract